2016
DOI: 10.1111/gfs.12220
|View full text |Cite
|
Sign up to set email alerts
|

Seed dormancy and dormancy‐breaking methods in Leymus chinensis (Trin.) Tzvel. (Poaceae)

Abstract: Leymus chinensis (Trin.) Tzvel. is a perennial grass with high productivity and forage value; however, poor stand establishment, often due to seed dormancy, limits its widespread use for forage production. To investigate the mechanism of seed dormancy and to develop effective methods of improving germination, the contribution of each part of the caryopsis to dormancy was investigated, and a number of single or combined dormancy-breaking pre-treatments were conducted using three seed lots. The palea, lemma, per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…However, the low germination rate (10–20%) with deep dormancy affects rapid and uniform seed germination in sheepgrass production and further blocks its wide application and the attainment of its expected value (Ma et al , 2010 b ). Approaches such as fluctuating temperature or the application of plant hormones, removal of the hull (palea and lemma), and mechanical resistance have been used in dormancy breaking and germination (Ma et al , 2010 a ; Hu et al , 2012; He et al , 2016). Although our understanding of seed dormancy and germination is well advanced in some model plants and important crops (Himi et al , 2011; Jia et al , 2012), little is known about the molecular mechanism of seed dormancy in sheepgrass, and it will be important to select genes related to germination or dormancy for molecular breeding.…”
Section: Introductionmentioning
confidence: 99%
“…However, the low germination rate (10–20%) with deep dormancy affects rapid and uniform seed germination in sheepgrass production and further blocks its wide application and the attainment of its expected value (Ma et al , 2010 b ). Approaches such as fluctuating temperature or the application of plant hormones, removal of the hull (palea and lemma), and mechanical resistance have been used in dormancy breaking and germination (Ma et al , 2010 a ; Hu et al , 2012; He et al , 2016). Although our understanding of seed dormancy and germination is well advanced in some model plants and important crops (Himi et al , 2011; Jia et al , 2012), little is known about the molecular mechanism of seed dormancy in sheepgrass, and it will be important to select genes related to germination or dormancy for molecular breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Seed hulls are one of the key factors that restrict seed germination, and the mechanical properties of seed hulls may have a certain obstacle-like effect on the exchange of gas and water [28]. He et al [29] mentioned in their study on seed dormancy of L. chinensis that seed hulls accounted for 28.4% of the causes of dormancy induction, and hulled seeds treated with GA 3 also exhibited a signi cantly reduced percentage of seed dormancy. Therefore, in this study, the main metabolic pathways involved in the treatment of hulls after GA 3 treatment and the main differentially abundant metabolites involved were explored.…”
Section: Effects Of Ga 3 On Hulls Of Leymus Chinensis Seedsmentioning
confidence: 99%
“…Previous studies on the seed dormancy and germination of sheepgrass have mostly focused on dormancy-breaking methods and the environmental and hormonal effects on germination (He et al, 2016; Zhang et al, 2006). The mechanical restriction of the lemma is considered to be the major cause of sheepgrass seed dormancy because removing the lemma can significantly increase germination (Ma et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical restriction of the lemma is considered to be the major cause of sheepgrass seed dormancy because removing the lemma can significantly increase germination (Ma et al, 2008). Furthermore, it was reported that the seed dormancy of sheepgrass was significantly affected by the lemma, palea, pericarp/testa, and endosperm of the seed, and their average contribution to seed dormancy was 23.4%, 6.2%, 28.4%, and 42.0%, respectively (He et al, 2016). However, the ecological and physiological role of the lemma was revealed; it plays important roles in water uptake, dehydration and salt tolerance during germination (Lin et al, 2016a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation